Pengaruh Pemberian Jarak Tanam dan Ukuran Umbi Bibit terhadap Pertumbuhan dan Hasil Tanaman Kentang (Solanum tuberosum L.) - Arisandi, Firman Rosidi; Sulistiyowati, Retno; Lidyana, Novita (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
This study aims to: 1) Knowing the influence of planting distance on the growth and yield of potato crops (Solanum tuberosum L.). 2) Know the effect of the size of seed bulbs on the growth and yield of potato plants (Solanum tuberosum L.). 3) Know the interaction between planting distance and the size of seed bulbs to the growth and yield of potato crops (Solanum tuberosum L.). Hypothesis: 1) Planting distance has a real influence on the growth and yield of potato crops (Solanum tuberosum L.). 2) The size of seed bulbs has a real influence on the growth and yield of potato crops (Solanum tuberosum L.). 3) There is an interaction between the influence of planting distance and the size of seed bulbs on the growth and yield of potato crops (Solanum tuberosum L.).This study uses a Factorial RandomIzed Group Design (RAK) with 2 factors, namely planting distance (J) as much as 4 levels of treatment and the size of seed bulbs (U) as many as 3 levels of treatment with 3 repeats. If the results of the F test show a noticeable effect then the analysis continues Duncan's Multiple Distance Test (DMRT) at a distance of 5%. Conclusion:1) The treatment of planting distance does not affect all observations on potato plants. 2) The treatment of seed bulb size + 30 gr (U3) has the best results, namely on the height parameters of the plant, the number of main stems, the number of branches, the number of bulbs per plant, the number of bulbs per plot, the weight of bulbs per plot, wet brangkasan per plant, wet brangkasan per plot, dry brangkasan per plant, dry brangkasan per plot. 3) The interaction between the treatment of planting distance and the treatment of seed bulb size does not affect all observations on potato plants.Keywords: printed normally, written alphabetically